ANALISIS PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, LEVERAGE DAN KOMISARIS INDEPENDEN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Tiya Lutfiana, 12.05.52.0084; Kartika, Andi (Students Journal of Accounting and Banking, 2016)
The study aims to examined and analyze the effect of firm size, firm age, leverage, and independent commissioner of intellectual capital disclosure. The population inthis study was the manufacturer that had been regrestered at indonesia Stock Exchange period from 2010 to 2014. The sampling method used a purposive sampling. Testing and analysing the effect of variabel used double regression analysis method. The study result showed that the firm size and firm age has positive affect and significant to intellectual capital disclosure. Whereas the leverage and the independent commisioner had negative effect and significant to intellectual capital disclosure. Keywords:Â Firm Size, Firm Age, Leverage, Independent Commissioner of Intellectual Capital Disclosure